Engineering Thermodynamics: Work and Heat Transfer - Rogers (Gordon); Mayhew (Yon) (2006)
Thermodynamics
43373a.jpg;43373b.jpg;43373c.jpg;43373d.jpg;43373e.jpg;43373f.jpg;43373g.jpg;43373h.jpg
22.5
Keywords: Thermodynamics